Extending the theory of information poverty to deepfake technology - Walter Matli (International Journal of Information Management Data Insights)
The advent of deepfake technology has introduced complex challenges to the information technology landscape, simultaneously presenting benefits and novel risks and ethical considerations. This paper delves into the evolution of deepfakes through the prism of information poverty theory, scrutinising how deepfakes may contribute to a growing information access/use inequality. The research focuses on the risks of misinformation and the ensuing expansion of digital divides, particularly when manipulative media could delude individuals lacking access to legitimate information sources. The study outlines the potential exacerbation of information asymmetries and examines the societal implications across various demographics. By integrating an analytical discussion on the risks associated with deepfakes, the study aligns the observed trends with the theoretical underpinnings of information poverty. As part of its contribution, the paper offers actionable policy-making recommendations and educational strategies to combat the proliferation of harmful deepfake content. The article aims to ensure a more equitable distribution of authentic information and foster media literacy. Through a multifaceted approach, this study endeavours to provide a foundational understanding for stakeholders to navigate the ethical minefield posed by deepfakes and to instil a framework for information equity in the digital era. The article provides critical insights into the discourse on deepfake technology and its relation to information poverty, underscoring the urgent need for equitable access to informed digital spaces. As deepfake technology evolves and more data emerges, a societal demand exists for comprehensive knowledge about deepfakes to promote discernment, decision-making and awareness. Policymakers are tasked with recognising the significance of widening access to sophisticated information technologies whilst addressing their negative repercussions. Their efforts will be particularly crucial for disseminating knowledge about deepfakes to those with limited or non-existent information and communication awareness and infrastructures. Learning from past successes and failures becomes pivotal in shaping effective strategies to address the challenges posed by deepfakes and fostering accessible, informed digital communities.